Narration as a constituent part of the mediation in english fiction conflict discourse - Chornii, Anastasiia; Чорній, А. Л.; Чорній, Анастасія Любомирівна (Одеса, 2018)
У статті розглянуто взаємозв'язок наративних конструкцій у процесі медіації та відтворення медіативних кореляцій в англомовній художній літературі, проаналізовано їхні спільності та виокремлено мовні ідентичності кожного із інструментів. Художня література виступає інструментом масового впливу на суспільство, поширюючи не лише ідею чи піднімаючи проблеми, але й відображає превалюючий спосіб роботи із цими ж проблемами, включаючи і шляхи вирішення конфлікту. Майстром відтворення цих ідей та настроїв стає або оповідач, або персонаж твору. Оповідач є незамінним учасником художнього твору, на якого покладається завдання «вести» читача крізь «історію письменника» при цьому, враховувати можливі гострі моменти, породжені внутрішніми або зовнішніми факторами. Так, суб'єктами конфлікту в англомовній художній література постає не лише конфлікт між людьми, але й між людиною та природою, людиною та суспільством, людиною та її цінностями. У цей час роль оповідача перетворююча на роль медіатора, завданням якого постає знайти оптимальний шлях примирення сторін у конфліктному діалозі. Ідея наративної медіації полягає у тому, аби заохотити сторони «розповісти свою історію», тим самим виразити власне бачення і звернути увагу на принципові моменти сприйняття ситуації. Роль медіатора за таких обставин полягає утому, аби відтворити ситуацію у позитивно спрямованому ключі, тим самим зменшити конфліктність та показати можливість пошуку оптимальних рішень задля примирення.

The article deals with the idea of correlation between narration and mediation in English speaking fiction, its similarities and differences while expressing the conflict position of opponents. Fiction as a part of an influential tool towards society depicts not only the particular idea within the concrete setting but also shows the main streams of people's outlook towards the double sense situations that produce a conflict. Dispute resolution ideas take place either in performance of a narrator or a character within fictional discourse. Narrator as a part of unchangeable element of fiction is formally the prominent character who is entitled to lead the reader within the plot taking into account internal (man versus self-conflict) and external conflict of characters such as man versus man, man versus nature, man versus society and man versus fate. At the same time the role of a narrator can be transformed to the model of mediator's behaviour whose aim is to find an appropriate resolution of a conflict for both opposite parties either within the conflict dialogue or controversial ideas depicted in English speaking fiction discourse. The idea of narrative mediation is to encourage the conflicting parties to tell their personal "story" of the conflict and reach resolution through a profound understanding of the context of their individual stories. The narrative perception is that people tend to organize their experiences in a story form where the narrative metaphor draws attention to the ways in which we use stories to make sense of lives and relationships. At the same time mediators who use a narrative orientation are interested in the constitutive properties of conflict stories that help to create a context from which a preferred story line can be developed and to build trust to the mediator and to the mediation process, develop externalizing conversations, map the effects of the problem on the person, deconstruct the dominant story lines character within fictional discourse. Narrator as a part of unchangeable element of fiction is formally the prominent character who is entitled to lead the reader within the plot taking into account internal (man versus self-conflict) and external conflict of characters such as man versus man, man versus nature, man versus society and man versus fate. At the same time the role of a narrator can be transformed to the model of mediator's behaviour whose aim is to find an appropriate resolution of a conflict for both opposite parties either within the conflict dialogue or controversial ideas depicted in English speaking fiction discourse. The idea of narrative mediation is to encourage the conflicting parties to tell their personal "story" of the conflict and reach resolution through a profound understanding of the context of their individual stories. The narrative perception is that people tend to organize their experiences in a story form where the narrative metaphor draws attention to the ways in which we use stories to make sense of lives and relationships. At the same time mediators who use a narrative orientation are interested in the constitutive properties of conflict stories that help to create a context from which a preferred story line can be developed and to build trust to the mediator and to the mediation process, develop externalizing conversations, map the effects of the problem on the person, deconstruct the dominant story lines and develop shared meanings about the conflict and its solutions.
Chornii, Anastasiia. Narration as a constituent part of the mediation in english fiction conflict discourse / A. Chornii // Одеський лінгвістичний вісник. – 2018. – Вип. 11. – С. 86-92.D0І https://doi.org/10.32837/2312-3192-2018-11-86-92
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Наративна медіація; нарація; конфлікт; оповідач; посередник; поведінка медіатора; англомовна художня література; Narrative mediation; narration; conflict; narrator; mediator; mediator's behavior; English speaking fiction